Thermal oxidation and hydroxyapatite coating of SLMed 316L stainless steel substrates - Rahil Izzati, Mohd Asri (2018)
316L Stainless Steel (316L SS) is one of the metallic biomaterials that commonly applied as a metal implant in the biomedical field as substitute or function restoration of degenerated tissues or organs. In this study, 316L SS taken as the metal substrate and fabricated through to additive manufacturing (AM) technology which is via selective laser melting (SLM) process. Concerning the corrosion issue of 316L SS, thermal oxidation (TO) and hydroxyapatite (HAp) coating were introduced in this study. The TO was conducted at 700 °C for 150, 200 and 250 h to develop oxide layer formation. The thermally oxidised SLMed 316L SS substrates were investigated based on a surface characterisation and a corrosion behaviour. The optimum condition for TO then continues with the HAp coating application. Sol-gel dip coating coated the non-oxidised and thermally oxidised SLMed 316L SS substrates and sintered at 500 °C for 1 h. The effect of TO and HAp coating were examined on the SLMed 316L SS substrates. The weight percentage of the SLMed substrates and the thickness of oxide layer increased with the increment of soaking time during TO. The iron oxide (Fe2O3) was detected as the oxide layer on thermally oxidised substrates. However, chromium oxide (Cr2O3) was detected on thermally oxidised for 150 h. In this study, only TO for 150 h showed improvement in corrosion behaviour due to the presence of Fe2O3 and Cr2O3 layers. Prolonged soaking time shows no improvement in corrosion behaviour. Consequently, the thermally oxidised SLMed 316L SS substrates for condition 150 h have proceeded to coat with HAp. The HAp coating on thermally oxidised SLMed 316L SS substrates exhibited thicker coating deposition and free crack coatings surface compared to coated non-oxidised SLMed substrates. Based on corrosion result, it confirmed the formation of the oxide layer and HAp coating able to enhance corrosion resistance of the SLMed 316L SS. The corrosion rate for coated thermally oxidised SLMed substrates is the lowest compared to other substrate conditions. The presence of oxide layers on the coated thermally oxidised SLMed 316L SS substrates show a significant difference in the corrosion behaviour due to the presence of Cr2O3 and Fe2O3 layers. It concluded that the oxide layers and HAp coating formed on thermally oxidised SLMed substrate gave full support to enhance corrosion behaviour of the SLMed substrate. Introducing new fabrication method for metallic biomaterials with presence of oxide layer and HAp coating was able to improve corrosion behaviour of 316L SS. The values of corrosion rate for all SLMed 316L conditions were also acceptable and tolerable compared to others conventional fabrication methods.